The Effect of Service Quality and Price on Purchase Decisions on Panoramic Trains - Mahesa , Nenden Tiara Oktafiani; Tahmat, Tahmat (International Journal of Management and Digital Business, 2026)
Transportation is a very important means of supporting the economy, social life, and daily activities for the community. One of the state- owned companies engaged in transportation is PT. Kereta Api Indonesia (Persero). PT. KAI has added the latest special train, one of which is the Panoramic Train, this train has only been operating for 2 years but the decrease in the number of passengers in the last year has reached 10% every month. Of course, this raises questions about the inconsistency of the quality of service and the prices provided to panoramic trainsThe purpose of this study is to find out and analyze partially and simultaneously the influence of service quality and price on purchasing decisions on panoramic trains (Daop 2 Bandung). This research includes descriptive and verifiable research with a quantitative approach. The population in this study is 2,898 panoramic train passengers. The sample technique used was based on the probability sampling technique with the type of simple random sampling so that a sample of 97 people was obtained. This data was collected using questionnaires that have been tested for validity and reliability tests. The data analysis technique used in this study uses a multiple linear regression analysis test with a significant level of 5% or 0.05. The programs and applications used to conduct data analysis and processing are using the IMB Statistical Package for Social Sciences (SPSS) Version 25Based on the results of the research obtained that: 1) There is a simultaneous significant influence of the independent variables of Service Quality and Price on the dependent variable in the form of Purchase Decision 2) the Service Quality variable has a partially significant effect on the Purchase Decision variable 3) the Price variable has a partially significant effect on the Purchase Decision variable. Based on the results of the respondents' answers regarding the quality of service is in the fairly good category, based on the results of the respondents' answers regarding the price is in the fairly good category, based on the results of the respondents' answers regarding the purchase decision is in the fairly good category